Cotyledonoid dissecting leiomyoma treated by laparoscopic surgery: A case report. Issue 2 (22nd April 2013) - Tanaka, Hirohiko; Toriyabe, Kuniaki; Senda, Tokihiro; Sakakura, Yasufumi; Yoshida, Kayo; Asakura, Tetsuo; Taniguchi, Haruki; Nagao, Kenji
Abstract A cotyledonoid dissecting leiomyoma is categorized as a leiomyoma with an unusual growth pattern, which is characterized by remarkable extrauterine bulbous growth in continuity with a dissecting myometrial component. A 36‐year‐old patient was preoperatively diagnosed with a mature cystic teratoma of the left ovary, and according to MRI, the tumor protruded from the uterus into the right broad ligament and was 10 cm in diameter. She underwent laparoscopic surgery to resect ovarian teratoma and the tumor under the right broad ligament. The tumor was almost completely resected and diagnosed as a cotyledonoid dissecting leiomyoma based on intraoperative and pathological findings. Recurrence was not seen for 26 months postoperatively in our case. Gross specimens are often mistaken for malignant lesions, but this was a benign disease. Even if some remnants of the leiomyoma remained postoperatively, recurrence has never been reported. When a cotyledonoid dissecting leiomyoma is resected laparoscopically, intrapelvic structures around it, such as the ureter, uterine artery, bladder, rectum and external iliac vessels, must be given careful attention.